2013
DOI: 10.1002/prot.24226
|View full text |Cite
|
Sign up to set email alerts
|

Disorder and order in unfolded and disordered peptides and proteins: A view derived from tripeptide conformational analysis. II. Tripeptides with short side chains populating asx and β‐type like turn conformations

Abstract: In the preceding paper, we found that ensembles of tripeptides with long or bulky chains can include up to 20% of various turns. Here, we determine the structural and thermodynamic characteristics of GxG peptides with short polar and/or ionizable central residues (D, N, C), whose conformational distributions exhibit higher than average percentage (>20%) of turn conformations. To probe the side-chain conformations of these peptides, we determined the (3)J(H(α),H(β)) coupling constants and derived the population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
129
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(140 citation statements)
references
References 68 publications
11
129
0
Order By: Relevance
“…Unblocked peptides have the advantage of providing a better spectral resolution in the structure‐sensitive amide I′ region than blocked peptides. In agreement with Grdadolnik et al and Shi et al , their data reveal a dominant sampling of the pPII/β‐strand region of the Ramachandran plot, but they also showed that residues with charged and polar amino acid residues can sample a variety of turn like conformations . Their pPII fractions varied between 0.72 for A and approximately 0.2 for aspartic acid (D p ).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Unblocked peptides have the advantage of providing a better spectral resolution in the structure‐sensitive amide I′ region than blocked peptides. In agreement with Grdadolnik et al and Shi et al , their data reveal a dominant sampling of the pPII/β‐strand region of the Ramachandran plot, but they also showed that residues with charged and polar amino acid residues can sample a variety of turn like conformations . Their pPII fractions varied between 0.72 for A and approximately 0.2 for aspartic acid (D p ).…”
Section: Introductionsupporting
confidence: 86%
“…The values for Δ G ( T R ) were calculated from the pPII/β mole fraction ratio obtained from the conformational analysis . Eqn is based on the experimentally backed assumption that even in the presence of multiple conformers, the temperature dependence of the Gibbs energy landscape can practically be accounted for by a two‐state model, which assumes that the population of minor turn fractions does not change with temperature …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, residues with hydrophobic and bulky side chains like valine or isoleucine prefer a more extended β‐strand‐like conformation over pPII 4c,g,i,j,o. 5 Interestingly, the polar protonated aspartic acid residue exhibits the largest β‐strand‐to‐pPII ratio, which might reflect stabilization by side chain–backbone hydrogen bonding 4k,n. Generally, all residues show a much larger preference for the pPII/β‐strand region (70–80 %) and a lesser tendency to populate right‐handed helical regions (4–15 %) 4n,o.…”
Section: Introductionmentioning
confidence: 99%
“…This observation indicates that the population of turn conformations might not be very temperature dependent, in agreement with recent theoretical predictions and experimental results. 83, 91 For the C-terminal residue, we obtained pPII fractions of 0.67, 0.60, for cationic and zwitterionic AAA, respectively.…”
Section: Resultsmentioning
confidence: 99%